2018
DOI: 10.1093/jas/sky251
|View full text |Cite
|
Sign up to set email alerts
|

New recombinant fibrolytic enzymes for improved in vitro ruminal fiber degradability of barley straw1

Abstract: This study used a high-throughput in vitro microassay, in vitro batch culture, and the Rumen Simulation Technique (RUSITEC) to screen recombinant fibrolytic enzymes for their ability to increase the ruminal fiber degradability of barley straw. Eleven different recombinant enzymes in combination with a crude mixture of rumen enzymes (50% recombinant enzyme:50% crude mixture of rumen enzymes) were compared with the crude mixture of rumen enzymes alone. In the microassay, all treatments were applied at 15 mg of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 36 publications
(59 reference statements)
10
27
0
1
Order By: Relevance
“…Torok and colleagues (Torok et al, 2008) investigated changes in gut microbial population in response to the supplementation of an NSP-degrading enzyme (containing βglucanase, xylanase, and protease activities) in a barley-based diet in chickens, and the results showed that microbial composition revealed distinct clusters correlating with un-supplemented and enzyme supplemented birds. Previous research reported that the pre-treatment of feed stuffs with carbohydrases can cause the release of reducing sugars and other hydrolysis materials, promoting chemotactic response in specific bacteria, and stimulating their attachment to feed particles, and thereby growth of these microbes (Beauchemin et al, 2003;Giraldo et al, 2007;Ribeiro et al, 2015Ribeiro et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Torok and colleagues (Torok et al, 2008) investigated changes in gut microbial population in response to the supplementation of an NSP-degrading enzyme (containing βglucanase, xylanase, and protease activities) in a barley-based diet in chickens, and the results showed that microbial composition revealed distinct clusters correlating with un-supplemented and enzyme supplemented birds. Previous research reported that the pre-treatment of feed stuffs with carbohydrases can cause the release of reducing sugars and other hydrolysis materials, promoting chemotactic response in specific bacteria, and stimulating their attachment to feed particles, and thereby growth of these microbes (Beauchemin et al, 2003;Giraldo et al, 2007;Ribeiro et al, 2015Ribeiro et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Individual bags were then placed in 125 mL serum vials. Rumen uid from 4-5 different sites within rumen was collected from four ruminally cannulated Angus x Hereford heifers fed 50% grass hay, 30% barley straw, 15% corn dried distillers grains plus solubles and 5% mineral/vitamin supplement (DM basis) [13]. Collected rumen uid was strained through cheesecloth and equal volumes from each cow were combined.…”
Section: Methodsmentioning
confidence: 99%
“…Collected rumen uid was strained through cheesecloth and equal volumes from each cow were combined. The inoculum was prepared by mixing rumen uid 1:4 with mineral buffer [13]. Inoculum (65 mL) was transferred to each vial under a stream of O 2 -free CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…All the observations above were supported by former reports that feed processed by carbohydrase enzymes could stimulate growth of speci c microbes (Wang et al 2001;Giraldo et al 2007;Giraldo et al 2008). It can be speculated that the pretreatment of feed stuffs with carbohydrases causes the release of hydrolysis materials (presumably oligosaccharides), which promote the chemotactic response of speci c bacteria, and stimulates their attachment to feed particles, thereby leading to growth of these microbes (Giraldo et al 2007;Beauchemin et al 2003;Ribeiro et al 2015;Ribeiro et al 2018).…”
Section: Cell Wall Polysaccharides Composition Of Differently Pretreamentioning
confidence: 99%
“…Torok and colleagues (Torok et al 2008) investigated changes in gut microbial population in response to the supplementation of an NSP-degrading enzyme (containing β-glucanase, xylanase, and protease activities) in a barley-based diet in chickens, and the results showed that microbial composition revealed distinct clusters correlating with un-supplemented and enzyme supplemented birds. Previous research reported that the pretreatment of feed stuffs with carbohydrases can cause the release of reducing sugars and other hydrolysis materials, promoting chemotactic response in speci c bacteria, and stimulating their attachment to feed particles, and thereby growth of these microbes (Giraldo et al 2007;Beauchemin et al 2003;Ribeiro et al 2015;Ribeiro et al 2018).…”
Section: Introductionmentioning
confidence: 99%